2015
DOI: 10.1016/j.ijpara.2015.05.003
|View full text |Cite
|
Sign up to set email alerts
|

RNA interference in adult Ascaris suum – an opportunity for the development of a functional genomics platform that supports organism-, tissue- and cell-based biology in a nematode parasite

Abstract: Graphical abstract

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
38
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 45 publications
(40 citation statements)
references
References 26 publications
1
38
0
1
Order By: Relevance
“…S1). Variable transcript knockdown was also observed in other A. suum tissues injected IP with dsRNA in a previous study (McCoy et al, 2015), which may reflect differences in cellular uptake, relative abundances of target transcripts, or insufficient duration of the experiment (although 24 h was sufficient for other targets here).…”
Section: Resultssupporting
confidence: 61%
See 2 more Smart Citations
“…S1). Variable transcript knockdown was also observed in other A. suum tissues injected IP with dsRNA in a previous study (McCoy et al, 2015), which may reflect differences in cellular uptake, relative abundances of target transcripts, or insufficient duration of the experiment (although 24 h was sufficient for other targets here).…”
Section: Resultssupporting
confidence: 61%
“…Previous research showed that IP injection of dsRNA caused transcript knockdown in adult A. suum tissues (including intestinal/hypodermis tissue), but intestine-specific effects were not delineated (McCoy et al, 2015). We performed IP treatments with otherwise intact worms (intact head and tail) and observed significant knockdown of target transcripts from the middle region of the intestine (associated with reproductive tissue) using either dsRNA or hsiRNA (hpo-19, 4 μg; Fig.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Despite there being a published genome of B. malayi (38), functional and genomic studies of the modes of action of anthelmintics in filaria have been difficult, and there have been only a few successful reports of RNAi experiments in B. malayi (34,(39)(40)(41)(42)(43)(44)(45)(46)(47). Here, we are able to describe a reliable RNAi method, using soaking in dsRNA that we have coupled with movement phenotyping and patch clamp to study the effects of cholinergic anthelmintics on adult B. malayi in vitro.…”
Section: Discussionmentioning
confidence: 99%
“…Worms were maintained in Roswell Park Memorial Institute-1640 (RPMI-1640) medium, and viability was maintained in both systems for over two weeks. Dmitryjuk et al (2014) sustained adult A. suum in Ascaris ringer's solution (ARS) for 20 hours without any nutrient, while McCoy et al (2015) maintained A. suum for eight days in ARS without any nutrient. In contrast, only two studies have reported the in vitro maintenance of Parascaris spp.…”
Section: Introductionmentioning
confidence: 99%